IMPLEMENTASI DIGITAL LEADERSHIP KEPALA SEKOLAH DALAM SOSIALISASI KEBIJAKAN PENDIDIKAN: STUDI KASUS PADA SEKOLAH MENENGAH KEJURUAN SE-KECAMATAN MIJEN - Arif Rumiyadi; Sutama Sutama; Achmad Fathoni (STKIP Pesisir Selatan, 2026)
Digital transformation in education requires school principals to develop adaptive leadership capabilities in managing change, including the process of educational policy dissemination. This study aims to analyze the implementation of digital leadership among school principals in disseminating educational policies at vocational high schools in Mijen District. This research employed a qualitative approach using a case study design. Data were collected through semi-structured interviews, observation, and documentation. Research participants were selected using purposive sampling, involving school principals, vice principals, teachers, and educational staff who were directly involved in school policy implementation. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings reveal that digital leadership plays an important role in developing technology-based policy communication, improving information dissemination effectiveness, and strengthening digital culture within schools. The implementation of digital leadership is supported by organizational readiness, technological facilities, and openness among school members. However, challenges remain, including differences in digital competence and adaptation to technological changes. This study contributes to the development of digital leadership studies in educational management and provides practical implications for strengthening digital transformation strategies in schools.